Different behaviors of organic matter under physical-biological controls in the eastern Indian Ocean - Zhang, Yixue; Wu, Ying; Zhang, Jing; Xu, Yi; Huang, Ke; Jin, Jie; Dai, Jinlong; Ye, Qi; Li, Jian; Zhang, Zhenqiu (Frontiers in Marine Science, 2023)
Marine organic matter (OM) pools are the key to understanding biogeochemical cycles and carbon storage, especially under ongoing ocean warming. The tropical eastern Indian Ocean (IO) is ideal for unraveling marine OM pools for being one of the least understood ocean basins in terms of its complex physical and biogeochemical dynamics. So far, OM transformation and export remain underexplored and enigmatic in the IO. Here, we integrated in situ observations and incubation experiments in the Central IO (CIO) and Bay of Bengal (BoB). A large OM pool was found in the CIO, where we emphasized the prominent contribution of production in the deep euphotic layer, with physical forcing seasonally playing a supporting role. The dissolved organic matter (DOM)-degradation experiment results revealed high efficiency of in situ DOM consumption in the BoB, whereas dark carbon fixation by ammonia-oxidizing microorganisms was considered an alternative strategy in the euphotic CIO. Water mixing was found to highly influence the OM pools in the mesopelagic waters in the tropical eastern IO, but active microbial respiration could also regulate the OM degradation in the CIO. Our results emphasized the heterogeneity of OM pools between the BoB and CIO, and stated their different regulators of carbon reservoir considering an ocean warming scenario.